2017
DOI: 10.29252/cmm.3.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of esterase and hemolysin activities of different Candida species isolated from vulvovaginitis cases in Lorestan Province, Iran

Abstract: Background and Purpose:Annually affecting millions of women, vulvovaginal candidiasis (VVC) is commonly described by signs and symptoms of vulvovaginal inflammation in the presence of Candida species. Today, the detection of the virulence factors plays a major role in the understanding of pathogenesis of candidiasis and helps produce new anticandidial drugs to improve its treatment efficiency. Herein, we aimed to evaluate the esterase and hemolysin activities of the vaginal isolates of Candida and their relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
4
4
0
1
Order By: Relevance
“…Recently, Noori et al in a study on Candida species isolated from individuals with vulvovaginal candidiasis showed no sig-nificant relationship between esterase production and the presence of VVC. Their results are similar to our study findings (38). Most Candida species isolated from humans secrete three groups of hydrolytic enzymes including phospholipase, proteinase, and esterase following the mycelial growth, which can facilitate their active penetration into host cells; they can be identified by quantitative and qualitative methods as virulence factors (39,40).…”
Section: One Of the Virulence Factors In Oral Candidiasis Is Thesupporting
confidence: 91%
“…Recently, Noori et al in a study on Candida species isolated from individuals with vulvovaginal candidiasis showed no sig-nificant relationship between esterase production and the presence of VVC. Their results are similar to our study findings (38). Most Candida species isolated from humans secrete three groups of hydrolytic enzymes including phospholipase, proteinase, and esterase following the mycelial growth, which can facilitate their active penetration into host cells; they can be identified by quantitative and qualitative methods as virulence factors (39,40).…”
Section: One Of the Virulence Factors In Oral Candidiasis Is Thesupporting
confidence: 91%
“…Hemolysin is important for pathogenicity as it imparts the survival capacity to the Candida. Based on the findings of a previous study [ 32 ], the highest hemolytic activity was observed in C. glabrata (72.7%), C. tropicalis (72.7%), and C. albicans (66.6%), while in the present study, it was the highest in C. albicans (85.5%), C. glabrata (70%) and C. tropicalis (59.4%). As it was a laboratory-based study, the actual prevalence of Candida infection in the community could not be determined, and it was further supplemented by the COVID-19 pandemic and lock downs throughout India.…”
Section: Discussionsupporting
confidence: 78%
“…The VVC is a highly common problem in diabetic women, owing to a number of factors, such as increase of vaginal mucosa due to the high deposition of glycogen in vaginal tissue [6]. According to the results of the research conducted around the world, the most common causative agent of VVC is Candida albicans (77-95%), followed by non-albicans Candida (NAC) species (20-30%) [7][8][9]. However, the results of the recent studies are indicative of the growing increase of NAC species [10,11].…”
Section: Introductionmentioning
confidence: 99%